Preoperative Systemic Immune–Inflammation Index (SII) as a Superior Predictor of Long-Term Survival Outcome in Patients With Stage I–II Gastric Cancer After Radical Surgery - He, Kang; Si, Lixiang; Pan, Xiaohua; Sun, Ling; Wang, Yajing; Lu, Jianwei; Wang, Xiaohua (Frontiers in Oncology, 2022)
Background Systemic immune-inflammation index (SII), calculated by immunoinflammatory cell counts of peripheral blood, is considered as a predictor of survival outcome in several solid tumor, including gastric cancer (GC). However, there is no study focus on the prognostic value of SII in early stage of GC. This study aims to compare prognostic prediction capabilities of several inflammatory indices, nutritional indices and tumor markers to further verify the superior prognostic value of SII in stage I-II GC patients after surgery. Methods 548 patients (358 in training group, and 190 in validation group) with stage I-II GC after radical surgery were retrospectively analyzed. The peripheral blood indices of interest were SII, NLR, PLR, MLR, ALI, SIS, PNI, BMI, albumin, CEA, CA125, CA19-9 and AFP. The t-ROC curves and the AUC were used to determine optimal cut-off value and prognostic ability of each parameter. Kaplan-Meier curves and multivariable Cox regression models were used to evaluate independent prognostic factors. The nomogram was constructed based on the result of bidirectional stepwise regression model. Results The optimal cut-off value of SII was 508.3. The 5-year overall survival rate of the SII-L group was significantly higher than that of the SII-H group (92% vs 80%, P<0.001), especially in the elderly and stage II patients (91% vs 73%, P=0.001; 86% vs 67%, P=0.003, respectively). The significant prognostic value of SII were consistent in most subgroup. In multivariate analysis, SII and CA19-9 were the only two independent prognostic hematology indices. The AUC value of SII (0.624) was greater than that of CA19-9 (0.528) and other prognostic parameters. Adding SII to conventional model improved the predictive ability of 5-year overall survival as shown by the significantly increased NRI, IDI (P=0.033, P=0.053, respectively) and modestly improved C-index (increased by 1.6%). External validation of SII-based nomogram demonstrated favorable predicative performance and discrimination. In addition, interactive web dynamic nomogram was published to facilitate clinical use. Conclusion SII is a simple but powerful index with high predictive value to predict survival outcome in patients with stage I-II GC after radical operation. The SII-based nomogram can provide intuitive and accurate prognosis prediction of individual patients.